Pancratistatin Inhibits the Growth of Colorectal Cancer Cells by Inducing Apoptosis, Autophagy, and G2/M Cell Cycle Arrest - Xiong, Yong (Med Sci Monit, 2019)
BACKGROUND: Worldwide, colorectal cancer is ranked as the third most prevalent cancer. The natural compound, pancratistatin, extracted from the spider lily, has previously been shown to target apoptosis in cancer cells lines. This study aimed to investigate the effects of pancratistatin in human colorectal cancer cells in vitro. MATERIAL/METHODS: Human colorectal cancer cell lines, including HTC-15 cells, were compared with a normal human colonic fibroblast cell line, CDD-18Co. Cells were treated with increasing doses of pancratistatin. The MTT assay was used to assess cell viability. Fluorescence microscopy using DAPI and Annexin-V/propidium iodide (PI) was used to detect cell apoptosis. Cell autophagy was detected by electron microscopy. Cell migration was evaluated using a wound healing assay, and Western blot determined the expression levels of cell cycle proteins. RESULTS: Pancratistatin inhibited the growth of the colorectal cancer cells with an IC(50) ranging from 15–25 μM, but had a limited effect in normal CCD-18Co cells, with an IC(50) of >100 μM. Pancratistatin reduced HCT-15 cell migration. Growth inhibition due to pancratistatin was associated with morphological changes of HCT-15 cells and included autophagy and apoptosis, and increased expression the autophagic proteins, LC3II, beclin-1, and Bax. Pancratistatin induced arrest of HCT-15 cells at G2/M of the cell cycle and inhibited phosphorylation of cdc2/cyclin-dependent kinase 1 (CDK1) and Cdc25c and the expression of cyclin B1. CONCLUSIONS: Pancratistatin inhibited the growth of colorectal cancer cells in vitro by inducing apoptosis, autophagy, and G2/M cell cycle arrest.